STRATEGIES TO IMPROVE THE INTENT OF IMPLEMENTING DIGITAL BUSINESS MODELS IN WHOLESALE CLOTHING MSMES - Rezky Naufal Pratama; M. Syamsul Ma'arif; Arry Ekananta (RADJA PUBLIKA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, particularly in the wholesale clothing sector centered in Tanah Abang. Despite the rapid growth of digital infrastructure and e-commerce, most wholesale clothing MSMEs still operate conventionally and have not adopted digital business models. This low adoption rate is influenced by various internal and external factors, including technological understanding, perceived usefulness of digitalization, and organizational readiness. This study aims to identify factors that influence the level of digital readiness (e-readiness) among wholesale clothing MSMEs, examine their effect on the intention to adopt digital business models (e-business), and formulate strategies to increase such intention. The research focuses on wholesale clothing MSMEs located in Pusat Grosir Metro Tanah Abang. A quantitative method was applied using Structural Equation Modeling – Partial Least Squares (SEM-PLS) to examine the predictive relationships between e-readiness, Technology Acceptance Model (TAM) variables, and e-business adoption intention. The Fuzzy Analytical Hierarchy Process (FAHP) was used to prioritize strategies based on expert judgment. The findings indicate that Perceived Organizational e-Readiness (POER) has the most significant influence on the intention to adopt e-business, particularly through the mediating roles of Perceived Ease of Use and Perceived Usefulness. In contrast, external factors such as government and market support (Perceived External e-Readiness/PEER) showed no significant effect. This suggests that internal organizational preparedness plays a more critical role than external conditions in shaping digital transformation intentions. The proposed strategic priorities include establishing a digital community among MSME actors, enhancing digital literacy through continuous training, and designating successful digital MSMEs as role models. These findings highlight the need to strengthen internal capacities before pushing for external collaboration. The implications of this study provide practical insights for policymakers, MSME associations, and business actors to design effective interventions to accelerate the adoption of digital business models.